African Vegetables (Clerodendrum volibile Leaf and Irvingia gabonensis Seed Extracts) Effectively Mitigate Trastuzumab Induced Cardiotoxicity in Wistar Rats - Akinsola Akinyele O (Oxidative Medicine and Cellular Longevity, 2020)
Trastuzumab (TZM) is a humanized monoclonal antibody that has been approved for the clinical management of HER2-positive metastatic breast and gastric cancers but its use is limited by its cumulative dose and off-target cardiotoxicity. Unfortunately, till date, there is no approved antidote to this off-target toxicity. Therefore, an acute study was designed at investigating the protective potential and mechanism(s) of CVE and IGE in TZM-induced cardiotoxicity utilizing cardiac enzyme and oxidative stress markers and histopathological endpoints. 400mg/kg/day CVE and IGE dissolved in 5% DMSO in sterile water were investigated in Wistar rats injected with 2.25mg/kg/day/i.p. route of TZM for 7 days, using serum cTnI and LDH, complete lipid profile, cardiac tissue oxidative stress markers assays, and histopathological examination of TZM-intoxicated heart tissue. Results showed that 400mg/kg/day CVE and IGE profoundly attenuated increases in the serum cTnI and LDH levels but caused no significant alterations in the serum lipids and weight gain pattern in the treated rats. CVE and IGE profoundly attenuated alterations in the cardiac tissue oxidative stress markers’ activities while improving TZM-associated cardiac histological lesions. These results suggest that CVE and IGE could be mediating its cardioprotection via antioxidant, free radical scavenging, and antithrombotic mechanisms, thus, highlighting the therapeutic potentials of CVE and IGE in the management of TZM-mediated cardiotoxicity.